Encapsulated fusion protein confers "sense and respond" activity to chitosan–alginate capsules to manipulate bacterial quorum sensing. Issue 2 (18th September 2012) - Gupta, Apoorv; Terrell, Jessica L.; Fernandes, Rohan; Dowling, Matthew B.; Payne, Gregory F.; Raghavan, Srinivasa R.; Bentley, William E.
Abstract: We demonstrate that "nanofactory"‐loaded biopolymer capsules placed in the midst of a bacterial population can direct bacterial communication. Quorum sensing (QS) is a process by which bacteria communicate through small‐molecules, such as autoinducer‐2 (AI‐2), leading to collective behaviors such as virulence and biofilm formation. In our approach, a "nanofactory" construct is created, which comprises an antibody complexed with a fusion protein that produces AI‐2. These nanofactories are entrapped within capsules formed by electrostatic complexation of cationic (chitosan) and anionic (sodium alginate) biopolymers. The chitosan capsule shell is crosslinked by tripolyphosphate (TPP) to confer structural integrity. The capsule shell is impermeable to the encapsulated nanofactories, but freely permeable to small molecules. In turn, the capsules are able to take in substrates from the external medium via diffusion, and convert these via the nanofactories into AI‐2, which then diffuses out. The exported AI‐2 is shown to stimulate QS responses in vicinal Escherichia coli. Directing bacterial population behavior has potential applications in next‐generation antimicrobial therapy and pathogen detection. We also envision such capsules to be akin to artificial "cells" that can participate in native biological signaling and communicate in real‐time with the human microbiome. Through such interaction capabilities, these "cells" may sense the health of the microbiome, and direct its function in a desired, host‐friendly manner. Biotechnol. Bioeng. 2013; 110: 552–562. © 2012 Wiley Periodicals, Inc. Abstract : Chitosan–alginate capsules were formed and subsequently loaded with an AI‐2 synthase "nanofactory" to modulate QS activity in Escherichia coli . We propose that biologically inspired carriers of molecular synthesis systems in native settings can modulate bacterial populations, including those of the human microbiome.